Influência da geocélula preenchida com resíduos de pedras preciosas no comportamento de um solo arenoso - Favretto, Julia (2018)
Rapid urban development, associated with the expansion of industrial poles and the growth of infrastructure works, have resulted in increased demand for space. As a consequence, there is a need for the construction industries to work with soil improvement techniques, in order to enable works in inadequate places and with unfavorable geotechnical conditions. One of the alternatives to improve the resistance of foundations is using geocell reinforcement, which consists in a tridimensional confinement structure, whose main function is to improve the performance and to increase the load capacity of the soil foundation system. In order to reduce the consumption of natural aggregates and to reuse residual materials, the geocells can be filled with precious gem processing waste. In this context, the present work aimed to study the influence of geocells filled with this residue on the behavior of a sandy soil, through plate load tests carried out in the laboratory. The reinforcement system was installed over the sand subgrade and submitted to static loading in a circular plate. Two geocell heights were tested in order to verify the effect of this parameter on the bearing capacity of the soil. Unreinforced tests, in the same heights, were also performed to compare and analyze the performance of thefoundation. The results indicate that the use of geocell leads to a significant increase in the soil resistance, with no influence of reinforcement height.